Isolation and Characterization of 5-Ethylhentriacontane and Nonacosane from Salvia plebeia - Tripathi, S.K.; Asthana, R.K.; Ali, Abid (Asian Journal of Chemistry, 2010)
Two aliphatic compounds isolated from aerial parts of Salvia plebeia have been characterized as 5-ethylhentriacontane and nonacosane by spectral data and chemical studies.